Latent Tuberculosis Infection and Residual Post-Tuberculous Changes in Children - Tatyana Y. Tyulkova; Alesya V. Mezentseva (Вопросы современной педиатрии)
The review of modern literature presents the results of studies characterizing the development mechanisms of latent tuberculosis infection and residual post-tuberculous changes in children. It was  noted that with the introduction of new technologies (computer  programs, immunological tests) into the practice of a  phthisiopaediatrician, small calcified foci in the intrathoracic lymph  nodes and lungs, previously invisible with traditional radiation  methods of examination (plan radiography, fluorography), began to  be detected more often. The authors concluded that the special state of mycobacteria, which form in individuals with a special type of  immune system, is essential. This determines the state of latent  microbism underlying the development of latent tuberculosis  infection and residual posttuberculous changes in children.